2022
DOI: 10.32604/jrm.2022.018146
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance on Torrefaction Valorization and Application of Biochar from Agricultural Waste for Soil Remediation

Abstract: With the increase of global proportion of soil pollution and the number of areas at risk, researchers have sought to develop various pathways to repair or relieve the pollutants in soil. Among them, biochar represents one multidimensional soil amendment which has got great deal of attention on its physicochemical properties towards the removal or mitigation of contaminants in soil. A variety of agricultural wastes like straw and manure prepared from different torrefaction process have been employed as feedstoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The removal of phosphate can rely on electrostatic adsorption between systems and complexation by ligand exchange, but most studies have shown that the removal of NO3relies on redox reactions. For example, Su Kai et al [32] found that structural ferrous iron on the surface of modified montmorillonite removes NO3from water by a redox reaction with nitrate. In the system studied in this paper, only lanthanum has the ability to redox, and Na is slightly more metallic than La, La does not have the ability to replace Na + from the Na + -NO3system, so there are no conditions for redox reactions, so the adsorption process of NO3by the materials prepared in this paper mainly relies on the electrostatic gravitational force provided by La 3+ and St for the system.…”
Section: Adsorption Of No3 -mentioning
confidence: 99%
“…The removal of phosphate can rely on electrostatic adsorption between systems and complexation by ligand exchange, but most studies have shown that the removal of NO3relies on redox reactions. For example, Su Kai et al [32] found that structural ferrous iron on the surface of modified montmorillonite removes NO3from water by a redox reaction with nitrate. In the system studied in this paper, only lanthanum has the ability to redox, and Na is slightly more metallic than La, La does not have the ability to replace Na + from the Na + -NO3system, so there are no conditions for redox reactions, so the adsorption process of NO3by the materials prepared in this paper mainly relies on the electrostatic gravitational force provided by La 3+ and St for the system.…”
Section: Adsorption Of No3 -mentioning
confidence: 99%